The Happiness Philosophers : The Lives and Works of the Great Utilitarians - Schultz, Bart (Book collections on Project MUSE., 2017)
Bart Schultz tells the colorful story of the lives and legacies of the founders of utilitarianism--one of the most influential yet misunderstood and maligned philosophies of the past two centuries. Best known for arguing that "it is the greatest happiness of the greatest number that is the measure of right and wrong," utilitarianism was developed by the radical philosophers, critics, and social reformers William Godwin (the husband of Mary Wollstonecraft and father of Mary Shelley), Jeremy Bentham, John Stuart and Harriet Taylor Mill, and Henry Sidgwick. Together, they had a profound influence on nineteenth-century reforms, in areas ranging from law, politics, and economics to morals, education, and women's rights. Their work transformed life in ways we take for granted today. Bentham even advocated the decriminalization of same-sex acts, decades before the cause was taken up by other activists. Yet in part because of its misleading name and the caricatures popularized by figures as varied as Dickens, Marx, and Foucault, utilitarianism is sometimes still dismissed as cold, calculating, inhuman, and simplistic. By revealing the fascinating human sides of the remarkable pioneers of utilitarianism, Schultz provides a richer understanding and appreciation of their philosophical and political perspectives - one that also helps explain why utilitarianism is experiencing a renaissance today and is again being used to tackle some of the world's most serious problems.